2018
DOI: 10.1111/jdv.15108
|View full text |Cite
|
Sign up to set email alerts
|

Imaging technique for the diagnosis of onychomatricoma

Abstract: Onychomatricoma is a rare tumour that derives from the nail matrix and grows within the nail plate. The clinical presentation can mimic many other tumours and conditions, and surgical biopsy and histopathological examination are necessary to confirm the diagnosis. As nail surgery is a painful experience for the patient and sometimes can leave permanent onychodistrophy, more precise preoperative diagnosis is needed to distinguish onychomatricoma from other nail diseases more accurately and to limit surgical int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…The digitations into the nail plate appears with a Y-shape and with a high-intensity signal, probably due to a concentration of water higher than that surrounding nail, and axial images can show the holes in the nail plate and the tumoural digitations [3, 13, 15]. To the best of our knowledge, there are no other lesions reported in the literature, neither benign nor malignant, that have the same presentation as OM on MRI.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The digitations into the nail plate appears with a Y-shape and with a high-intensity signal, probably due to a concentration of water higher than that surrounding nail, and axial images can show the holes in the nail plate and the tumoural digitations [3, 13, 15]. To the best of our knowledge, there are no other lesions reported in the literature, neither benign nor malignant, that have the same presentation as OM on MRI.…”
Section: Discussionmentioning
confidence: 86%
“…To the best of our knowledge, there are no other lesions reported in the literature, neither benign nor malignant, that have the same presentation as OM on MRI. However, in atypical presentations or clinical signs of malignancy, the diagnosis has to be confirmed by histopathology [3, 15, 16]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the anterior view of the free edge of the nail plate showed honeycomb-like cavities in 70% of the cases and a ruin appearance-the most common feature of onychomycosis-in 11% of the cases. 8 Although longitudinal striae may be observed in onychomycosis, splinter haemorrhages and honeycomb-like cavities are observed exclusively in onychomatricoma. 9 Third, the presence of confined solitary nail dystrophy for a long period can be a clue for diagnosing the underlying onychomatricoma.…”
Section: A Case Of Veiled Onychomatricomamentioning
confidence: 99%
“…Second, nail dermoscopy can reveal potential signs of an underlying onychomatricoma. 3 Cinotti et al 8 reported that the common dermoscopic features of the nail plate in patients with onychomatricoma are splinter haemorrhages (72%) and longitudinal white lines (71%); the latter corresponds to tumour digitations in the nail plate. Additionally, the anterior view of the free edge of the nail plate showed honeycomb-like cavities in 70% of the cases and a ruin appearance-the most common feature of onychomycosis-in 11% of the cases.…”
Section: A Case Of Veiled Onychomatricomamentioning
confidence: 99%
“…68), and splinter hemorrhages (Marchetti et al 2018;Okon et al 2017;Lesort et al 2015;Di Chiacchio et al 2013b). Other features include melanonychia, subungual hematoma, plate fracture, nail fold changes, and pterygium (Cinotti et al 2018;Di Chiacchio et al 2013b). Intraungual tumor projections from the nail matrix create characteristic honeycomb-like (or woodworm-like) cavities visible at the nail plate free edge.…”
Section: Onychomatricomamentioning
confidence: 99%